Field relationships, mineralogy and structural features of the Port Mouton pluton, southwestern Nova Scotia - Douma, S. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1992)
The Port Mouton pluton (PMP) of southern Nova Scotia is a complex, per aluminous, post-tectonic granitoid body that is distinct from other plutons and batholiths of the Meguma Terrane. The pluton consists of ten units, which collectively range in composition from tonalitc to trondhjemite, granodiorite, monzogranite, leucomonzogranite, aplite, pegmatite and lamprophyre. The PMP evolved in three mafic to felsic cycles defined by the initial mafic end-members for each cycle (units 1,4 and 7). These three units are the most volumetrically abundant of the ten units and unit 1 is the oldest. Shoshonitic lamprophyres intruded mid-way through cycle II and were subsequently intruded by units in cycle III. The PMP is at least 352 Ma (""""Ar^'Ar) and is demonstrably younger than the regional metamorphism of 395 Ma. Two distinct foliations observed within the pluton occur only in units 1 and 4. The foliation in unit 1 is perpendicular to the regional foliation of the country rocks and is probably of igneous origin. The local foliation in unit 4, the origin of which remains unknown, is perpendicular to that in unit 1 and parallel to the regional foliation in the country rocks. Contacts of the PMP with the host metasedimentary rocks are predominantly sharp, although minor migmatization is present locally. Le pluton de Port Mouton (PMP) du sud de la Nouvelle-écosse est une masse granitique complexe, pcralumineuse et post-tectonique, qui se distingue des autres plutons et batholites du terrain de Meguma. Le pluton consiste en dix unites, allant des tonalites aux trondhjemites, granodiorites, monzogranites, leucomonzogranites, aplites, pegmatites et lamprophyres.